The nucleolar ubiquitin-specific protease USP36 deubiquitinates and stabilizes c-Myc - Sun, Xiao-Xin (Proc Natl Acad Sci U S A, 2015)
c-Myc protein stability and activity are tightly regulated by the ubiquitin-proteasome system. Aberrant stabilization of c-Myc contributes to many human cancers. c-Myc is ubiquitinated by SCF(Fbw7) (a SKP1-cullin-1-F-box complex that contains the F-box and WD repeat domain-containing 7, Fbw7, as the F-box protein) and several other ubiquitin ligases, whereas it is deubiquitinated and stabilized by ubiquitin-specific protease (USP) 28. The bulk of c-Myc degradation appears to occur in the nucleolus. However, whether c-Myc is regulated by deubiquitination in the nucleolus is not known. Here, we report that the nucleolar deubiquitinating enzyme USP36 is a novel c-Myc deubiquitinase. USP36 interacts with and deubiquitinates c-Myc in cells and in vitro, leading to the stabilization of c-Myc. This USP36 regulation of c-Myc occurs in the nucleolus. Interestingly, USP36 interacts with the nucleolar Fbw7γ but not the nucleoplasmic Fbw7α. However, it abolished c-Myc degradation mediated both by Fbw7γ and by Fbw7α. Consistently, knockdown of USP36 reduces the levels of c-Myc and suppresses cell proliferation. We further show that USP36 itself is a c-Myc target gene, suggesting that USP36 and c-Myc form a positive feedback regulatory loop. High expression levels of USP36 are found in a subset of human breast and lung cancers. Altogether, these results identified USP36 as a crucial and bono fide deubiquitinating enzyme controlling c-Myc’s nucleolar degradation pathway.